Case report: Early onset de novo FSGS in a child after kidney transplantation—a successful treatment - Carvajal Abreu, Karla; Loos, Sebastian; Fischer, Lutz; Pape, Lars; Wiech, Thorsten; Kemper, Markus J.; Tönshoff, Burkhard; Oh, Jun; Schild, Raphael (Frontiers in Pediatrics, 2023)
Background: Early onset de novo focal segmental glomerular sclerosis (FSGS) in the kidney allograft in patients without FSGS in the native kidney is a rare disorder in children. It usually occurs mostly beyond the first year after kidney transplantation and often leads to graft loss.Standardized treatment protocols have not yet been established.We describe a boy with early onset de novo FSGS in the transplanted kidney and non-selective glomerular proteinuria (maximum albumin-to-creatinine ratio of 3.8 g/g; normal range, ≤0.03 g/g creatinine). Manifestation occurred at 30 days posttransplant and was accompanied by a significant graft dysfunction (eGFR 61 mL/min per 1.73 m 2 ). Treatment with 25 sessions of plasmapheresis over 14 weeks and three consecutive days of methylprednisolone pulse therapy (10 mg/kg per day) followed by oral prednisolone as rejection prophylaxis (3.73 mg/m 2 per day) led to sustained remission of proteinuria (albuminto-creatinine ratio of 0.028 g/g) and normalization of graft function (eGFR 92 mL/min per 1.73m 2 ) after 14 weeks. The follow-up period was 36 months.This case underlines the efficacy of immunosuppressive and antibody eliminating therapy in early onset de novo FSGS after kidney transplantation.